2023
DOI: 10.1101/2023.01.07.523115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Ecology of Viruses in Urban Rodents with a Focus on SARS-CoV-2

Abstract: Wild animals are naturally infected with a range of viruses, some of which may be zoonotic for humans. During the human COIVD pandemic there was also the possibility of rodents acquiring SARS-CoV-2 from people, so-called reverse zoonoses. To investigate this we have sampled rats (Rattus norvegicus) and mice (Apodemus sylvaticus) from urban environments in 2020 during the human COVID-19 pandemic. We metagenomically sequenced lung and gut tissue and faeces for viruses, PCR screened for SARS-CoV-2, and serologica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 63 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…Virus typing based on the partial RdRp sequences revealed that the viruses found in Berlin rats belong to the genus Alphacoronavirus and are closely related to each other (99.4-100.0% identity on nucleotide level) and to the Lucheng Rn rat coronavirus (Figure 1B). Hence, in contrast to SARS-CoV-2, rodent-associated alphacoronaviruses appear to circulate in the investigated rat population, which is in line with previous studies investigating coronaviruses in rats (2,5).…”
Section: Main Textsupporting
confidence: 90%
See 2 more Smart Citations
“…Virus typing based on the partial RdRp sequences revealed that the viruses found in Berlin rats belong to the genus Alphacoronavirus and are closely related to each other (99.4-100.0% identity on nucleotide level) and to the Lucheng Rn rat coronavirus (Figure 1B). Hence, in contrast to SARS-CoV-2, rodent-associated alphacoronaviruses appear to circulate in the investigated rat population, which is in line with previous studies investigating coronaviruses in rats (2,5).…”
Section: Main Textsupporting
confidence: 90%
“…Since the pandemic unfolded, it was speculated about the role of animals as amplifying or reservoir hosts. Because of the long-term association between rodents and coronaviruses (1) , the wide range of coronaviruses occurring in wild rodents (2) and the ubiquitous distribution of commensal rodents, it was obvious to also include rodents in susceptibility studies, among them rats. Under experimental conditions using high infection doses, rats were reported as receptive particularly to the SARS-CoV-2 delta variant of concern (VOC), but also experimental infection with other variants like alpha, beta or omicron were described (3,4) , posing the theoretical risk for establishing effective infection chains in nature.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…SARS-CoV-2 infection in Muridae such as house mice (Mus musculus) and brown rats (Rattus norvegicus) may depend on the virus strain: initial studies with the original (Wuhan) strains of the virus failed to infect them [20,21] and field studies failed to demonstrate evidence of infection in wild populations (27 Mus musculus and 97 R. norvegicus). Later variants did however cause infection in laboratory studies [21][22][23][24] and there have been several subsequent field reports of sporadic infection of rats [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…SARS-CoV-2 infection in Muridae such as house mice (Mus musculus) and brown rats (Rattus norvegicus) may depend on the virus strain: initial studies with the original (Wuhan) strains of the virus failed to infect them (Dinnon, Leist et al 2020, Shuai, Chan et al 2021 and field studies failed to demonstrate evidence of infection in wild populations (27 M.musculus and 97 R.Norvegicus). Later variants did however cause infection in laboratory studies (Gu, Chen et al 2020, Shuai, Chan et al 2021, Halfmann, Iida et al 2022, Zhang, Cui et al 2022 and there have been several subsequent t field reports of sporadic infection of rats (Fisher, Airey et al 2023, Robinson, Kotwa et al 2023, Wang, Lenoch et al 2023).…”
Section: Introductionmentioning
confidence: 98%